Bioconjugation of quantum dot luminescent probes for Western blot analysis. (October 2005) - Makride, Savvas C.; Gasbarro, Christina; Bello, Job M.
Western blot analysis is a widely used technique for protein immunodetection. Its current format, however, is unsuitable for multiplex detection of proteins, primarily due to intrinsic limitations of standard organic dyes employed as probes. Quantum dot (QD) semiconductor nanoparticles exhibit significant advantages over organic dyes, including their broad absorption bands, narrow, tunable, and symmetric emission spectra, large Stokes shifts, and excellent photostability. Here we describe a novel method for the functionalization ofstrepta-vidin-coated QDs with an in vivo biotinylated peptide (head-to-tail dimerized Z domain derived from protein A) that permits the facile conjugation of antibodies to QDs. In this study, we demonstrate the simultaneous detection of two different types of protein in a Western blot. The bioconjugation of QDs described here makes it possible to achieve multiplex detection of proteins in Western blot analysis in a more straightforward manner.